2005
DOI: 10.1007/s10652-005-5226-1
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ferry Traffic as a Qualitatively New Forcing Factor of Environmental Processes in Non-Tidal Sea Areas: A Case Study in Tallinn Bay, Baltic Sea

Abstract: The impact of wake wash from high-speed ferries on the coastal environment in non-tidal seas is analysed in terms of wave energy and power, and properties of the largest waves. Shown is that hydrodynamic loads caused by heavy high-speed traffic may play a decisive role not only in low-energy coasts but also in certain areas with high wind wave activity. For example, ship-generated waves form, at least, about 5-8% from the total wave energy and about 18-35% from the wave power in the coastal areas of Tallinn Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Often, the latter are not considered in the context of WLF, although they can have a major impact on the abiotic and biotic processes in the littoral zone. Several studies have investigated the impact of short-term WLF on coastal and shelf regions (Clark, 1997;Eriksson et al, 2004;Soomere, 2005;Erm & Soomere, 2006). Only a few investigations, however, have focused on lake-littoral zones (Luettich et al, 1990;Eggleton et al, 2004;Scheifhacken, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Often, the latter are not considered in the context of WLF, although they can have a major impact on the abiotic and biotic processes in the littoral zone. Several studies have investigated the impact of short-term WLF on coastal and shelf regions (Clark, 1997;Eriksson et al, 2004;Soomere, 2005;Erm & Soomere, 2006). Only a few investigations, however, have focused on lake-littoral zones (Luettich et al, 1990;Eggleton et al, 2004;Scheifhacken, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly fast ferries show a high ratio of propulsion power to vessel displacement as it is a precondition for reaching high speeds. This, together with near-critical and supercritical speeds, leads to high loads on the coastal environment [39]. This has been confirmed in a series of studies conducted at Tallinn Bay, Estonia [37,39,[42][43][44].…”
Section: Environmental Issuesmentioning
confidence: 71%
“…The massive growth in exhaust emissions per passenger-mile and the great increase in external noise and waves generated by large high-speed ships are the major concerns of environmental studies [37][38][39]. Additionally, environmental impact studies on fast ferries have found that, whereas hull shape have little effect on resistance or wash, water depth [40] and the displacement/length ratio have a significant effect.…”
Section: Environmental Issuesmentioning
confidence: 99%
“…It is commonly believed that the largest environmental impacts come from long and long-crested almost nondispersive wave groups of significant amplitude [6,7]. Another recognized hazard is caused by solitonic waves that may result in high water velocities [8], elevate water levels at the shore [9] or build rogue waves [10].…”
Section: Introductionmentioning
confidence: 99%